Historische Rahmenbedingungen der Deutschen Einigung von 1871 - Kraus , Hans-Christof (Pázmány Law Review, 2023)
The article briefly outlines the emergence of German political unity in the 19th century against the background of the collapse of the old German Empire (1806). While the rigid internal structures of the German Confederation, founded in 1815, prevented an agreement for a long time, political unity could only be established after 1856. The decisive factor for this was the „Crimean War situation”, i.e. a political situation in which the four major European powers (Russia, France, Great Britain, Austria) did not want to or could not prevent the foundation of a German empire.